Rivaroxaban-induced spontaneous hemothorax: a rare case report and literature review - Xiaolong Li; Shuhao Xu; Chunfang Zeng; Ding Han; Xin Wang (Frontiers in Medicine)
IntroductionRivaroxaban, a novel oral anticoagulant, is widely used in patients with non-valvular atrial fibrillation. Bleeding events during rivaroxaban therapy most commonly include gastrointestinal bleeding and intracranial hemorrhage, while spontaneous hemothorax is exceedingly rare. We report a case of spontaneous hemothorax occurring during rivaroxaban administration.MethodsWe report the case of a patient presenting primarily with dyspnea. The patient had been on long-term oral rivaroxaban for atrial fibrillation. Physical examination upon admission revealed diminished breath sounds in the left lung. Computed tomography imaging demonstrated a large left-sided pleural effusion with adjacent pulmonary atelectasis. Laboratory tests indicated significant coagulation abnormalities. After admission, the patient underwent therapeutic thoracentesis and chest tube placement, with bloody pleural fluid observed in the drainage. Due to the marked coagulation abnormalities on admission, the patient received fresh frozen plasma transfusion. Further history-taking revealed recent use of oral fluconazole. A review of the literature suggested that the spontaneous hemothorax might be associated with the concurrent use of rivaroxaban and fluconazole.ResultsFollowing treatment, a follow-up computed tomography scan 3 months later showed no evidence of recurrent hemothorax.DiscussionConcomitant administration of rivaroxaban and fluconazole significantly increases the risk of bleeding events, necessitating clinician vigilance regarding potential drug–drug interactions when formulating therapeutic regimens.